A community model for water-energy-food security nexus development: cultivating sustainable livelihoods and an adaptive comanagement approach in rural Mozambique - Lager, Zachary (Stellenbosch : Stellenbosch University, 2021)
Thesis (MPhil)--Stellenbosch University, 2021.